2005
DOI: 10.1117/12.638765
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced hydrocarbon contamination in vacuum

Abstract: We investigated laser-induced deposition processes on BK7 substrates under the influence of pulsed Q-switched Nd:YAG laser radiation, starting from small toluene partial pressures in a background vacuum environment. The composition and structure of the deposit was analyzed using microscopic methods like Nomarski DIC, dark-field and white-light interference microscopy, TEM, EDX and XPS. We found a distinct threshold for deposition built-up dependant on the partial pressure of toluene (0.2 J/cm 2 at 0.1 mbar, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Previous studies with nanosecond lasers under vacuum and sealed atmospheric conditions have shown that the useful lifetime of the optics and multiple pulse damage fluence reduced significantly for dielectric films [5][6][7][8] and bulk materials [9,10] compared to atmospheric conditions. Two explanations have been given for these observations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with nanosecond lasers under vacuum and sealed atmospheric conditions have shown that the useful lifetime of the optics and multiple pulse damage fluence reduced significantly for dielectric films [5][6][7][8] and bulk materials [9,10] compared to atmospheric conditions. Two explanations have been given for these observations.…”
Section: Introductionmentioning
confidence: 99%
“…LIC was proposed by Wernham et al during the research of frequency-tripped Nd:YAG lasers on space [11][12][13][14] . According to their research, LIC is caused by the interaction of the laser with molecules which outgas from organic materials in vacuum on the optical surfaces, and it will form highly absorbing deposits on the surface of optics.…”
Section: Determination Of the Pathway For Lic In Regenerative Amplifiersmentioning
confidence: 99%
“…Therefore, finding out origin of these optical damages is the priority to improve operation lifetime of the Regen. There are two possible reasons for such optical damages: one is that damage threshold of optical components in Regen cavity may be not high enough to prevent laser induced damages (LIDs), which result from defects on the surfaces or in the bodies of these components [8][9][10] ; the other is that laser induced contamination (LIC) may happened on the surfaces of optical components in the Regen cavity, i.e., the formation of highly absorbing deposits on optical surfaces caused by the interaction of the laser with molecules which outgas from organic materials in vacuum or molecules of dust and gas in contaminated air environment [11][12][13][14] . LIC results in degradation of the properties of optical components, which contributes to an overall transmission loss and eventual irreversible damages of optical components.…”
Section: Introductionmentioning
confidence: 99%
“…Specific test methods have recently been developed in the frame of ESA's Aeolus and Earthcare satellites [4]. For LIC testing, the coating is exposed to the laser beam in the presence of organic materials, and the resulting transmission loss is measured.…”
Section: B Laser Induced Contamination (Lic) / Laser Induced Damage mentioning
confidence: 99%